Institutional fragility and outward foreign direct investment from China - Shi, Weilei; Sun, Sunny Li; Yan, Daying; Zhu, Zhu (Journal of International Business Studies, 2017)
We develop the concept of institutional fragility to investigate the outward foreign direct investment (OFDI) behavior of firms from emerging economies. When different dimensions of institutions are not progressing at the same pace, internal friction and conflict arise during institutional development. Such fragility could push a firm to escape its home country as a strategic response. Using a sample of 578,360 Chinese firm-year observations over a 10-year period, we find that institutional fragility at the provincial level is associated with increased OFDI decision. This relationship is weaker when firms have high productivity or have been controlled by state with high ownership, stronger when firms have a high level of export network. Overall, our institutional fragility perspective extends and enriches the institution-based view and offers new insights into OFDI behavior.